2017
DOI: 10.1002/jor.23633
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of regional bone quality in cervical vertebrae considering BMD: Determining a safe trajectory for cervical pedicle screw fixation

Abstract: This study aimed to report the mechanical strength and characteristics of the lateral mass and pedicle considering BMD for the safe insertion of pedicle screws in the subaxial cervical level. We evaluated BMD and Hounsfield unit (HU) values of cortical bones at the lateral mass and pedicle of C3-7 from CT images in 99 patients. Patients were divided into three groups (Group A, T-score ≥ -1; Group B, -2.5 < T-score < -1.0; Group C, T-score ≤ -2.5). The HU numbers of cortical bone in the vertebral canal (medial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(52 reference statements)
0
4
0
1
Order By: Relevance
“…Several additional aspects were addressed in the present study. Studies demonstrated the strong influence of bone quality on the binding strength of the bone–screw interface, which is a crucial factor in stabilizing thoracolumbar implants 28,29 . However, few studies have focused on evaluating the relationship between pull‐out strength and local bone quality in the lateral mass of cervical segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several additional aspects were addressed in the present study. Studies demonstrated the strong influence of bone quality on the binding strength of the bone–screw interface, which is a crucial factor in stabilizing thoracolumbar implants 28,29 . However, few studies have focused on evaluating the relationship between pull‐out strength and local bone quality in the lateral mass of cervical segments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated the strong influence of bone quality on the binding strength of the bone-screw interface, which is a crucial factor in stabilizing thoracolumbar implants. 28,29 However, few studies have focused on evaluating the relationship between pull-out strength and local bone quality in the lateral mass of cervical segments. DEXA (Dual-energy X-ray absorptiometry), a two-dimensional technique, has been the most commonly used method to assess bone quality in studies.…”
Section: Sc-lms Provided More Fixation Stability After Pmma Injectionmentioning
confidence: 99%
“…They did not explain why contact of the medial wall of the lateral mass is important for finding the opening of the pedicle. Recently, only one study evaluated the strength of the medial cortex of the lateral mass [30]. Studies on the complications of CPS provided further indications on the proper screwing of the cervical pedicle; that is, major misplacements of CPS involving the transverse foramen occurred in the lateral part of the pedicle, but involvement of medial wall was relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…The medial wall of the lateral mass is stronger than the trabecular bones and other cortices of the nearby structures. 19 If the trajectory is chosen correctly, the surgeon feels the resistance of the medial cortex of the lateral mass, if introducing the probe. The tip of the mLMS should stop 1 to 2 mm anterior to the posterior wall of the vertebral body as seen on lateral fluoroscopic image ( Fig.…”
Section: Methodsmentioning
confidence: 99%